FACTORS ASSOCIATED WITH HYPERTENSION RECURRENCE AMONG OUTPATIENTS - Alkhusari Alkhusari; Erik Rosadi; Ikke Aulia Nabila (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Hypertension remains a major global health problem with a high prevalence and risk of recurrence. Based on health data in South Sumatra Province, hypertension continues to be one of the most common non-communicable diseases. At Rawa Bening Public Health Center, 1,131 hypertension cases were recorded from January to April 2025. This study aimed to determine the factors associated with hypertension recurrence among outpatients in the working area of Rawa Bening Public Health Center. This study used a quantitative analytic design with a cross-sectional approach. The population consisted of 1,131 patients with hypertension, and 92 respondents were selected using purposive sampling. Data were collected using questionnaires from June 27 to July 2, 2025. The variables included medication adherence, smoking habits, dietary patterns, and hypertension recurrence. Data were analyzed using the Chi-square test with a significance level of 5%. Results: The results showed that hypertension recurrence occurred in 63 respondents (68.5%). Most respondents had low medication adherence (70.7%), did not smoke (58.7%), and had poor dietary patterns (64.1%). There was a significant association between medication adherence and hypertension recurrence (p=0.007), smoking habits and hypertension recurrence (p=0.000), and dietary patterns and hypertension recurrence (p=0.011). Hypertension recurrence among outpatients is associated with medication adherence, smoking habits, and dietary patterns. These findings indicate that preventing hypertension recurrence should not only focus on pharmacological treatment but also on strengthening continuous education, monitoring medication adherence, controlling smoking behavior, and improving dietary patterns through promotive and preventive services at the primary health care level.